Pengaruh Brand Image Terhadap Keputusan Pembelian yang di Mediasi Brand Trust - Nur Aeni; Muhamad Ekhsan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The use of the internet causes changes in people's behaviour in making buying decisions. Purchases are not only made in a particular store or place but can be purchased online. The purpose of this study was to determine whether brand image influences purchasing decisions mediated by the trust of the Wardah brand cosmetics. This study uses quantitative methods using SEM Smart PLS software as an analysis tool. The number of samples obtained using the Slovin formula using random sampling techniques, namely as many as 88 respondents. Data collection uses a Google form to fill out an online questionnaire. The data analysis method used was the R-square test, Bootstrap, path coefficient, and specific indirect effects. The results showed that brand image affects purchase decisions, brand image affects brand trust, brand trust affects purchase decisions, and brand trust affects the relationship between brand image and purchase decisions. Retailers who can maintain brand image and brand trust will be able to increase customer decisions to buy cosmetic products online.